Transcriptomics and Metabolite Analysis Reveals the Molecular Mechanism of Anthocyanin Biosynthesis Branch Pathway in Different Senecio cruentus Cultivars - Jin, Xuehua; Huang, He; Wang, Lu; Sun, Yi; Dai, Silan (Frontiers in Plant Science, 2016)
The cyanidin (Cy), pelargonidin (Pg), and delphinidin (Dp) pathways are the three major branching anthocyanin biosynthesis pathways that regulate flavonoid metabolic flux and are responsible for red, orange, and blue flower colors, respectively. Different species have evolved to develop multiple regulation mechanisms that form the branched pathways. In the current study, five Senecio cruentus cultivars with different colors were investigated. We found that the white and yellow cultivars do not accumulate anthocyanin and that the blue, pink, and carmine cultivars mainly accumulate Dp, Pg, and Cy in differing densities. Subsequent transcriptome analysis determined that there were 43 unigenes encoding anthocyanin biosynthesis genes in the blue cultivar. We also combined chemical and transcriptomic analyses to investigate the major metabolic pathways that are related to the observed differences in flower pigmentation in the series of S. cruentus. The results showed that mutations of the ScbHLH17 and ScCHI1/2 coding regions abolish anthocyanin formation in the white and the yellow cultivars; the competition of the ScF3′H1, ScF3′5′H, and ScDFR1/2 genes for naringenin determines the differences in branching metabolic flux of the Cy, Dp, and Pg pathways. Our findings provide new insights into the regulation of anthocyanin branching and also supplement gene resources (including ScF3′5 ′H, ScF3′H, and ScDFRs) for flower color modification of ornamentals.